Pengembangan dan inovasi kurikulum berbasis sekolah dalam meningkatkan mutu pendidikan - Chika Falda Pasaribu; Iswantir Iswantir (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
School-Based Curriculum Development has become a strategic approach to improving educational quality in response to the challenges of the 21st century, including digital transformation, globalization, and the evolving demands of the workforce. This article aims to examine the concepts, objectives, components, processes, stakeholder roles, challenges, and optimization strategies of school-based curriculum development within the implementation of the Merdeka Curriculum. The study employs a literature review method by analyzing relevant and recent scholarly articles, journals, and educational policy documents. The findings indicate that school-based curriculum development provides educational institutions with the flexibility to design curricula that align with students’ characteristics, local potential, community needs, and advancements in science and technology. The main components of curriculum development include educational objectives, curriculum content, learning processes, and evaluation systems. Its successful implementation is highly dependent on teachers’ professional competence, effective school leadership, and active collaboration among stakeholders, including parents, school committees, communities, government agencies, and industry partners. However, several challenges remain, such as limited human resources, inadequate facilities and infrastructure, technological readiness issues, and insufficient stakeholder coordination. Therefore, strengthening educators’ capacity, developing context-based curricula, integrating digital technology, and conducting continuous evaluation are essential strategies for creating adaptive and innovative curricula that support the development of 21st-century competencies. Ultimately, school-based curriculum development serves as a key instrument for enhancing sustainable educational quality and preparing students to meet future challenges.